Stem/stromal cells for treatment of kidney injuries with focus on preclinical models - Torres Crigna, Adriana; Daniele, Cristina; Gamez, Carolina; Medina Balbuena, Sara; Pastene, Diego O.; Nardozi, Daniela; Brenna, Cinzia; Yard, Benito A.; Gretz, Norbert; Bieback, Karen (Frontiers in medicine, 2018)
Within the last years, the use of stem cells (embryonic, induced pluripotent stem cells or hematopoietic stem cells), Progenitor cells (e.g. endothelial progenitor cells) and most intensely mesenchymal stromal cells (MSC) has emerged as a promising cell-based therapy for several diseases including nephropathy. For patients with end-stage renal disease (ESRD), dialysis or finally organ transplantation are the only therapeutic modalities available. Since ESRD is associated with a high healthcare expenditure, MSC therapy represents an innovative approach. In a variety of preclinical and clinical studies, MSC have shown to exert renoprotective properties, mediated mainly by paracrine effects, immunomodulation, regulation of inflammation, secretion of several trophic factors, and possibly differentiation to renal precursors. However, studies are highly diverse; thus, knowledge is still limited regarding the exact mode of action, source of MSC in comparison to other stem cell types, administration route and dose, tracking of cells and documentation of therapeutic efficacy by new imaging techniques and tissue visualization. The aim of this review is to provide a summary of published studies of stem cell therapy in acute and chronic kidney injury, diabetic nephropathy, polycystic kidney disease, and kidney transplantation. Preclinical studies with allogeneic or xenogeneic cell therapy were first addressed, followed by a summary of clinical trials carried out with autologous or allogeneic hMSC. Studies were analyzed with respect to source of cell type, mechanism of action etc.